2003
DOI: 10.3168/jds.s0022-0302(03)73862-4
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of Aflatoxin M1 in Milk of Dairy Ewes Treated with Different Doses of Aflatoxin B1

Abstract: Two experiments were conducted to study the amount of aflatoxin M1 (AFM1) in milk in response to feeding aflatoxin B1 (AFB1). In experiment 1, four dairy ewes in early lactation received a single dose of pure AFB1 (2 mg). Individual milk samples were collected during the following 5 d to measure AFM1 concentration. The average excretion of AFM1 in milk followed an exponential decreasing pattern, with two intermediate peaks at 24 and 48 h. No AFM1 was detected in milk at 96 h after dosing. The mean rate of tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
115
5
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 13 publications
21
115
5
1
Order By: Relevance
“…The observed plateau developed later than in previous studies, in which the steady state for AFM1 was established at 24 (Frobish et al, 1986) and 76 h (Polan et al, 1974, Diaz et al, 2004) from the initial AFB1 ingestion, but is in agreement with results reported by Battacone et al (2003) on sheep, in which the observed plateau condition was between day 9 and day 13 from the first AFB1 ingestion. However, milk AFM1 levels in the present study were lower than previously reported maximum concentrations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The observed plateau developed later than in previous studies, in which the steady state for AFM1 was established at 24 (Frobish et al, 1986) and 76 h (Polan et al, 1974, Diaz et al, 2004) from the initial AFB1 ingestion, but is in agreement with results reported by Battacone et al (2003) on sheep, in which the observed plateau condition was between day 9 and day 13 from the first AFB1 ingestion. However, milk AFM1 levels in the present study were lower than previously reported maximum concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…Other factors that affect carryover (CO) into milk include species differences (Battacone et al, 2003), animal variability (Van Egmond, 1989;Steiner et al, 1990;Veldman et al, 1992) and mammary alveolar cell membrane health (Lafont et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data indicate that the chronic exposure of piglets to low mycotoxin levels still could affect the intestinal immune system and prolong infection with intestinal pathogens (Devriendt et al, 2009;Oswald et al, 2003). Based on the chemical structure and properties of Group B and G AF, they can easily pass through the plasma membrane of (for example) intestinal epithelial cells and rapidly appear in the blood circulation (Battacone et al, 2003;Gallo et al, 2008;Martins et al, 2007). Although the expression of major AF-metabolizing enzymes in intestinal epithelial cells is yet to be explored, detoxification of AF by these cells is minimal, and these highly carcinogenic AF can easily reach the blood stream.…”
Section: Discussionmentioning
confidence: 99%
“…This somewhat unexpected result against the general assumption that some of raw milk might have higher level of residue than processed milk in plants due to the dilution effect, could be explained as the difference in sampled source of brands. In those studies, they used 1) Limit of detection at ppt ND: not described the milk from single dairy company but we used various brands of milk from supermarket.…”
Section: Resultsmentioning
confidence: 99%
“…It is produced by molds and ingested into animal body through the contaminated feedstuffs during animal breeding. Once ingested by the animal it is rapidly absorbed by the gastrointestinal tract and is transformed from AFB1 into the metabolite AFM1 (Battacone et al, 2003). It has been demonstrated that up to 6% of the ingested AFB1 is secreted into the milk as AFM1 (Van Egmond and Dragacci, 2001) and, because it is relatively resistant to heat treatments, it is almost entirely retained in pasteurized milk, powdered milk, and infant formula.…”
Section: Introductionmentioning
confidence: 99%